IMPROVING STUDENT’S WRITING SKILL BY USING DIARY AT MTS AL-FATTAH MOJOKERTO - Maula Paramita; Triana Wuri Cahyanti; Caltira Rosiana (STKIP PGRI Nganjuk, 2023)
This study used the classroom action research (PTK) method, with a sample size of 24 students at MTs Al-Fattah Mojokerto for the 2022/2023 academic year. By using diary media to train students' writing skills, the research instruments were questionnaires, sheets, field notes, tests, and documentation. The data analysis technique in this study was the average pretest and posttest scores. if in cycle I there are several students who are not successful then the researcher holds cycle II and if in cycle II it is still not fulfilled then the researcher continues to cycle III, if it is felt that cycle III has been fulfilled then the cycle can be stopped. The results in this study the researchers completed in cycle III with satisfactory results, because in cycle I and cycle II it was felt that they did not meet the score set by the researcher Penelitian ini menggunakan metode penelitian tindakan kelas (PTK), dengan jumlah sampel sebanyak 24 siswa MTs Al-Fattah Mojokerto tahun ajaran 2022/2023. Dengan menggunakan media buku harian untuk melatih keterampilan menulis siswa, instrumen penelitiannya adalah angket, lembar, catatan lapangan, tes, dan dokumentasi. Teknik analisis data pada penelitian ini adalah rata-rata nilai pretest dan posttest. apabila pada siklus I ada beberapa siswa yang belum berhasil maka peneliti mengadakan siklus II dan apabila pada siklus II masih belum terpenuhi maka peneliti melanjutkan ke siklus III, jika dirasa siklus III sudah terpenuhi maka siklus dapat dilakukan. dihentikan. Hasil penelitian ini peneliti tuntaskan pada siklus III dengan hasil yang memuaskan, karena pada siklus I dan siklus II dirasa belum memenuhi nilai yang ditetapkan peneliti.